[PP.11.05] RESERVOIR-PRESSURE ANALYSIS IN TYPE 2 DIABETES INDIVIDUALS WITH CARDIOVASCULAR DISEASE. (September 2016) - Aizawa, K.; Casanova, F.; Mawson, D.; Elyas, S.; Adingupu, D.D.; Gooding, K.M.; Strain, W.D.; Park, C.M.; Parker, K.H.; Gates, P.E.; Shore, A.C.; Hughes, A.D.
Abstract : Objective: Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in type 2 diabetes (DM). Central artery haemodynamics may play an important role in the development of CVD in DM. Central haemodynamic indices derived from reservoir-pressure analysis (RPA) have recently been shown to predict cardiovascular events in several populations. However, it is unknown whether those indices are associated with CVD in DM. We aimed to determine the differences in RPA indices in DM individuals with and without CVD. Design and method: We studied 106 individuals with DM and CVD (DM+CVD+; 69.5 ± 8.9 yrs, 24F), 138 individuals with DM but without CVD (DM+CVD-; 65.5 ± 8.5 yrs, 49F), and 264 non-DM individuals with and without CVD (DM-; 65.9 ± 8.9 yrs, 89F). RPA indices including reservoir pressure integral (PRI), peak reservoir pressure (MAXPR), excess pressure integral (XSPI) and peak excess pressure (MAXXSP) were obtained by radial artery tonometry. Results: PRI and MAXPR were significantly lower in DM+CVD+ (84.4 ± 1.3 mmHg·s and 101.9 ± 0.4 mmHg) and DM+CVD- (82.7 ± 1.1 mmHg·s and 102.7 ± 0.4 mmHg) than DM- (90.8 ± 0.8 mmHg·s and 103.9 ± 0.3 mmHg, p<0.05) after adjustments for age, sex and mean arterial pressure (MAP). XSPI and MAXXSP were significantly higher in DM+CVD+ (7.2 ± 0.2 mmHg·s and 42.8 ± 0.8 mmHg) than DM+CVD- (6.1 ± 0.2 mmHg·s and 38.9 ± 0.7 mmHg) and DM-(6.4 ± 0.1 mmHg·s and 38.5 ± 0.5 mmHg, p < 0.05) after the same adjustments. Conclusions: These results demonstrate that the presence of DM is associated with reduced aortic reservoir function, which may result in a suboptimal left ventricular workload, contributing to the development of CVD. Our findings suggest a potential utility of excess pressure indices (XSPI and MAXXSP) for risk stratification in individuals with DM.